Impact of an Education Programme on IBD Patients' Skills: Results of a Randomised Controlled Multicentre Study [ECIPE]. (24th September 2020) - Moreau, J; Hammoudi, N; Marthey, L; Trang-Poisson, C; Nachury, M; Altwegg, R; Grimaud, J C; Orempuller, S; Hébuterne, X; Aubourg, A; Baudry, C; Seksik, P; et al.
Abstract: Background: Better patient knowledge on inflammatory bowel disease [IBD] could improve outcome and quality of life. The aim of this study was to assess if an education programme improves IBD patients' skills as regards their disease. Methods: The GETAID group conducted a prospective multicentre randomised controlled study. IBD patients were included at diagnosis, or after a significant event in the disease course. Patients were randomised between 'educated' or control groups for 6 months. Education was performed by trained health care professionals. A psycho-pedagogic score [ECIPE] was evaluated by a 'blinded' physician at baseline and after 6 and 12 months [M6 and M12]. The primary endpoint was the increase of ECIPE score at M6 of more than 20%. Results: A total of 263 patients were included in 19 centres (male:40%; median age:30.8; Crohn's disease [CD]:73%). Of these, 133 patients were randomised into the educated group and 130 into the control group. The median relative increase in ECIPE score at M6 was higher in the educated group as compared with the control group (16.7% [0–42.1%] vs 7% [0–18.8%], respectively, p = 0.0008). The primary endpoint was met in 46% vs 24% of the patients in the educated and control groups, respectively [ p = 0.0003]. A total of 92 patients met the primary endpoint. In multivariate analysis, predictors of an increase of at least 20% of the ECIPE score were randomisation in the educated group (odds ratio [OR] = 2.59) and no previous surgery [OR = 1.92]. Conclusions: These findings support the set-up of education programmes in centres involved in the management of IBD patients.